Investigating the preventive effects of pulsed electromagnetic fields on glucocorticoid-induced osteoporosis in rats - Shuai Ding; Guangquan Zhang; Yanzheng Gao; Zhiqiang Hou; Fuqiang Shao (Scientific Reports)
Abstract The use of pulsed electromagnetic field (PEMF) has demonstrated effectiveness in the management of femoral head osteonecrosis as well as nonunion fractures; however, the effects of PEMF on preventing glucocorticoid-induced osteoporosis (GIOP) have not been extensively studied. The aim of this investigation was to explore the effectiveness of PEMF stimulation in averting GIOP in rats and uncover the potential fundamental mechanisms involved. A total of seventy-two adult male Wistar rats composed the experimental group and were subsequently assigned to three groups for treatment. (1) On the first day (day 0), 24 rats in the PEMF group were intravenously injected with lipopolysaccharide (LPS) at a concentration of 10 μg/kg. This was followed by intramuscular injections of methylprednisolone acetate (MPSL) at a dose of 20 mg/kg for the subsequent three days (days 1–3). Subsequently, the rats were exposed to PEMF for 4 h daily, with the duration varying from 1 to 8 weeks. (2) Adhering to the injection schedule of the PEMF group, the MPSL group (consisting of 24 rats) was administered LPS and MPSL, omitting PEMF stimulation. (3) The PS group (n = 24) was administered injections of 0.9% saline solution in an identical manner and at the same time intervals as the other two groups. At 1, 2, 4, and 8 weeks after the last MPSL (or saline) injection, bone mineral density (BMD), bone mineral content (BMC), and the expression levels of bone morphogenetic protein-2 (BMP-2) mRNA and protein in the proximal femur were measured. Analysis of the PS and PEMF groups at 1, 2, 4, and 8 weeks after the final saline (or MPSL) injection revealed no statistically significant differences in BMD or BMC (P > 0.05). From weeks 2 through 8, the MPSL group rats displayed a marked decrease in BMD and BMC compared to those of the PS group, and at the 4-week and 8-week time points, these values were significantly lower than those of the PEMF group (P < 0.05). Compared with those in the MPSL and PS groups, the expression levels of BMP-2 mRNA markedly increased after PEMF treatment, peaking one week later and sustaining a heightened state for four weeks, but decreased only at the eighth week. Conversely, BMP-2 protein expression exhibited a similar upward trend, peaking two weeks after PEMF treatment and then remaining elevated for the subsequent eight weeks. PEMF stimulation has been shown to have prophylactic potential against GIOP in rats, possibly through the upregulation expression of BMP-2 expression.